(untitled) (The International Journal for Scientific Research, 2023)
This paper aims to achieve higher quality levels for information systems project management through proposing a quality assurance model for Information Systems Projects Management (IS-PM). This paper presents important quality concepts and fundamentals related to IS-PM. In addition, it presents the life cycle, phases, and activities of IS-PM. Depending on the proposed steps and a combination of statistical techniques, this paper introduces a proposed quality assurance model for IS-PM activities. This proposed model can be used for building a software tool for the quality assurance of IS-PM.